(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The content of detective works includes a mysterious murder, the causes of the crime, the search for the killer, the study and comparison of events, finding the criminal and the legal assessment of his actions. In such works, the crime and the process of its disclosure, events, persons, situations and processes associated with the crime are expressed through certain language units. Therefore, detective works occupy a special place in the study of the legal vocabulary of law students. The article talks about the significance of Tahir Malik’s detective work "Shaitanat" in the study of legal vocabulary and draws conclusions.